REST AREA CEMPAKA DI KELURAHAN CEMPAKA , BANJARBARU - Astuti, Hesti Dwi; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Cempaka is a strategic place for drivers to stop and rest because Cempaka has the potential of distinctive local products that attract drivers to stop and rest. But, this is not supported by adequate facilities. Drivers who stop by can only rest for a limited time with limited facilities. However, not a few drivers who force themselves to rest for a long time in food stalls, mosques or minimarkets, resulting in long queues and forcing visitors to park their vehicles on the shoulder of the road because of limited parking space. This is what underlies the planning of the rest area in Cempaka, with the concept of an integrated rest area, which makes this rest area integrated with the development of the existing potential in Cempaka.